Effects of anthropogenic noise on endocrine and reproductive function in White's treefrog, Litoria caerulea. (16th January 2015) - Kaiser, Kristine; Devito, Julia; Jones, Caitlin G.; Marentes, Adam; Perez, Rachel; Umeh, Lisa; Weickum, Regina M.; McGovern, Kathryn E.; Wilson, Emma H.; Saltzman, Wendy
Abstract : Urbanization brings the introduction of roads and anthropogenic noise. Noise has negative health outcomes across vertebrates. White's treefrogs ( Litoria caerulea ) exposed to ecologically relevant levels of traffic noise for one week had elevated circulating corticosterone levels and decreased sperm count and sperm viability relative to controls. Abstract : Urbanization is a major driver of ecological change and comes with a suite of habitat modifications, including alterations to the local temperature, precipitation, light and noise regimes. Although many recent studies have investigated the behavioural and ecological ramifications of urbanization, physiological work in this area has lagged. We tested the hypothesis that anthropogenic noise is a stressor for amphibians and that chronic exposure to such noise leads to reproductive suppression. In the laboratory, we exposed male White's treefrogs, Litoria caerulea, to conspecific chorus noise either alone or coupled with pre-recorded traffic noise nightly for 1 week. Frogs presented with anthropogenic noise had significantly higher circulating concentrations of corticosterone and significantly decreased sperm count and sperm viability than did control frogs. These results suggest that in addition to having behavioural and ecological effects, anthropogenic change might alter physiology and Darwinian fitness. Future work should integrate disparate fields such as behaviour, ecology and physiology to elucidate fully organisms' responses to habitat change.